A case series of neonatal human parecho-virus encephalitis with a seasonality and endemicity - Kudukkan, Favas; Athoor, Bindu; Neliyathodi, Fysal; Haweri, Sheela P. (International Journal of Contemporary Pediatrics, 2021)
Human parecho viruses are small, non-enveloped, single stranded RNA viruses within parechovirus genus of the large picornaviridae family. In new-born it can cause gastroenteritis, sepsis and encephalitis. We report case series of parecho-virus encephalitis admitted to a tertiary care centre, Perinthalmanna. Parechoviral encephalitis is an endemic disease seasonally present (May-July) in certain regions of Northern part of Kerala. HPeV are viruses that cause CNS infection in the neonatal period, resulting in white matter lesions that can be visualised with MRI. In a retrospective study, 4 newborn babies of neonatal HPeV encephalitis diagnosed on the basis of clinical and radiological findings with a seasonality were assessed. HPeV encephalitis needs to be in differential diagnosis when neonates and young infants present with seizure and sepsis. HPeV infection must be considered in infants with specific pattern of white matter change but no convincing history of a perinatal hypoxic-ischaemic insult.